Effect of luting space and cements on retention of implant supported crowns fabricated by laser sintering - Özgün Yusuf Özyılmaz (Selçuk University, 2017)
Background: The aim of this study was to evaluate the retention strength of five different cements used for implant supported crowns with two cement gap values.Methods: Standard titanium abutments were scanned by means of a 3D digital laser scanner. 100 standard metal copings were designed by a CAD/CAM system with two cement gap values (20 and 40μm). The copings were cemented to the abutments using the following five cements (n=10). Poly F (PF), GC FujiCEM (GCF), Rely X (RX), MIS Crown Set(MCS) and Multilink N (MN). The specimens were placed in 100% humudity for 24 hours then specimens were thermal cycled 1000 times. After thermal cycling specimens were subjected to a pull-out test using a universal testing machine at a 0.5 mm/min crosshead speed. The test results were analyzed with two-way ANOVA, followed by multiple comparisons using Tamhane tests (α=0.05).Results: Statistical analysis revealed that significant differences were observed among cement groups (p<0.05). PF and MN had the highest and the least mean retentive strength, respectively. No significant difference was found between RX and MCS. Increasing the cement gap from 20 to 40 μm improved retention significantly for each cement group (p<0.05).Conclusion: The ranking of cements presented in the study is meant to be an arbitrary guide for the clinician in deciding the appropriate cement selection for CAD/CAM fabricated metal copings onto implant abutments.